2019
DOI: 10.1038/s41436-018-0036-2
|View full text |Cite
|
Sign up to set email alerts
|

A gene-centric strategy for identifying disease-causing rare variants in dilated cardiomyopathy

Abstract: Rare variants in cardiomyopathy genes can be effectively stratified by combining variant-level and gene-level information. Prioritization of genes based on their a priori likelihood of disease causation is a key factor in identifying clinically actionable variants in cardiac genetic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
(3 reference statements)
1
21
0
Order By: Relevance
“…Recently, we found that in patients with severe forms of DCM, more than 50% of the HTx candidates might be affected by a genetic etiology (Klauke et al, 2017). Until now, rare variants in at least 40 different genes have been shown to be associated with DCM (Brodehl et al, 2019; Horvat et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found that in patients with severe forms of DCM, more than 50% of the HTx candidates might be affected by a genetic etiology (Klauke et al, 2017). Until now, rare variants in at least 40 different genes have been shown to be associated with DCM (Brodehl et al, 2019; Horvat et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ttnb is primarily expressed in skeletal muscle, and is not required for heart function, as loss of ttnb does not lead to cardiac defects [ 59 , 60 ]. Furthermore, ttnb is unable to compensate for the loss of ttna in the embryonic heart [ 43 , 59 , 61 , 62 , 63 ]. Importantly, Seeley et al (2007) provided a detailed annotation of ttna and ttnb exons in comparison to human TTN and confirmed that the cardinal splicing events that give rise to the main TTN isoforms are also conserved in zebrafish.…”
Section: Titin In the Heart: Insights From Zebrafishmentioning
confidence: 99%
“…As the lists of genes in commercial DCM panels grow, expert curation adds context for interpretation. Independent groups have identified genes that consistently accounted for pathogenic and likely pathogenic variants for DCM: TTN, MYH7, DSP, SCN5A, LMNA, TPM1, TNNC1, TNNT2, BAG3, PLN, RBM20, LDB3, DMD, DES, ACTC1, NEXN, and VCL [5,[38][39][40][41]. FLNC was subsequently identified as an important gene for DCM and should be included in this group [5].…”
Section: Genes Implicated In Monogenic Dominant Dcmmentioning
confidence: 99%
“…Titin TTN encodes the largest protein (~35,000 amino acids) expressed in the body. TTN protein spans one-half of the [5,[38][39][40][41]. Daggers indicates a MalaCards score greater than 100 [26] sarcomere from the Z disc to the M line and comprises four domains: the Z disc binding region, I band domain that overlaps sarcomeric actin filaments, A band domain that overlaps myosin filaments, and the M line binding region.…”
Section: Genes Implicated In Dcm: Recent Updatesmentioning
confidence: 99%
See 1 more Smart Citation